Congestion-Adaptive and Delay-Sensitive Multirate Routing Protocol in MANETs: A Cross-Layer Approach - Gawas, Mahadev A.; Gudino, Lucy J.; Anupama, K. R (Journal of Computer Networks and Communications, 2019)
With a growing demand of multimedia communication over MANETs, to support quality of service (QoS), the MAC standards such as 802.11a/b/g operate with multiple data rates to efficiently utilize the limited resources. Since the wireless channel is shared among the neighbors in MANETs, determining delay-sensitive and congestion-aware routes using the IEEE 802.11 MAC is still a challenging problem. This paper proposes a novel cross-layer approach called congestion-adaptive and delay-sensitive multirate (CADM) routing protocol in MANETs. The CADM protocol exploits the cross-layer interaction between the network layer, MAC, and physical layer. The CADM accesses the correlation between data rate, congestion metric, and MAC delay in delay-sensitive applications to provide enhanced network efficiency in MANETs. The protocol discovers multiple node-disjoint routes and facilitates optimal data rates between the links based on the estimated delay to admit a flow with the certain delay requirement in multirate MANETs. The proposed CADM protocol discovers the route through less congested nodes and also actively handles the congestion if it occurs. The performance of the CADM protocol is comprehensively assessed through the simulation, which highlights the advantages of our cross-layer mechanism.